Seasonal Variations of Serum Zinc Concentration in Adult Population: Tehran Lipid and Glucose Study - Sahar ASKARI; Golaleh ASGHARI; Hossein FARHADNEJAD; Arash GHANBARIAN; Parvin MIRMIRAN; Fereidoun AZIZI (Tehran University of Medical Sciences, 2019)
Background: Zinc, an essential trace element, plays a key role in many biological human body functions. Serum zinc concentration is the most widely used indicator of zinc status for general populations. Considering the limited data available on seasonal fluctuation of serum zinc concentration, we aimed at determining seasonal variations in serum zinc concentrations of Tehranian adults. Methods: The current study was conducted within the framework of the Tehran Lipid and Glucose Study, on 4698 subjects, aged ≥20 years. Serum zinc samples of subjects were obtained from all four seasons over three years (from 2009 to 2011); samples of similar seasons over three years were placed in one group and the geometric means of serum zinc concentration of four seasons were compared to determine possible seasonal variations. Results: Participants with mean age 46.3 yr and geometric mean of serum zinc concentration 116.3 µg/dl, were studied for almost three years through four seasons. Serum zinc concentrations in spring and summer were significantly higher than those in autumn and winter (112.2 and 114.4 vs. 106.7 and 104.8 µg/dl; P<0.001, respectively). Moreover, monthly serum zinc concentration of all subjects differed, with the lowest and highest levels found in October and August (98.5 vs. 122.7; P<0.001). Conclusion: This study demonstrates the difference in serum zinc concentration in Iranian adults of both genders in different months and seasons during the year.